A Review on Floating Microspheres as Gastro-retentive Drug Delivery System - Firke , Sagar N.; Roge , Ashish B.; Siraskar, Pritam R.; Ghiware, Nitin B. (Current Overview on Pharmaceutical Science Vol. 1, 2022)
Apart from providing improved bioavailability of poorly absorbed drugs and a required release profile, the Gatsroretentive drug delivery system has piqued the interest of pharmaceutical formulation scientists. For drugs with an absorption window in the upper small intestine, a controlled drug delivery system with a prolonged residence time in the stomach can be extremely useful. Tablets, capsules, pills, laminated films, granules, and powders are among the gastroretentive dosage forms available. Floating microspheres are one of many approaches to gastroretention, including mucoadhesion, flotation, sedimentation, expansion, modified shape systems, and so on. Floating microspheres have gained popularity due to their uniform distribution in the stomach, which results in more reproducible drug absorption and a lower risk of local irritation. These systems have several advantages over single-unit dosage forms. The current review briefly discusses the physiology of gastric emptying in relation to floating drug delivery systems. The drug is slowly released at the desired rate while the system floats over the gastric contents, resulting in increased gastro-retention time and reduced fluctuations in plasma drug concentration. The goal of this review is to compile the most recent literature on the method of preparation and various parameters influencing the performance and characterization of floating microspheres.